1993
DOI: 10.1159/000187526
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intravenous Administration of Recombinant Human Erythropoietin in Rats Subject to Hemorrhagic Shock

Abstract: The effects of recombinant human erythropoietin (rHuEPO) on survival and blood pressure in hypovolemic hemorrhagic shock in rats have been studied by intravenous administration. The hormone caused an increase in the time of survival compared to the group of rats without treatment (102 ± 4.5 vs. 25 ± 4.5 min, p < 0.01, vehicle; 102 ± 4.5 vs. 25 + 2 min, p < 0.01, saline solution) and an increase in the percentage of the surviving animals (5/7 after 120 min vs. 0/7, p < 0.05). The animals treated showed an incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…On studying the blood flow of the human pretibial muscle by means of 133 Xe clearance, Buemi et al [22] found an EPO-induced reduction in postischemic vasodilation. Moreover, in anesthetized rats subjected to hemorrhagic shock by intermittent bleeding, EPO administration significantly increased the mean arterial pressure, the survival time, and the percentage of animals surviving with respect to untreated controls [23] . EPO also seems to be able to inhibit acetylcholine-induced cutaneous vasodilation and can stimulate the endothelial release of endothelin and inhibit nitric oxide, a potent vasodilator [24] .…”
Section: Ph: the Erythropoietin (Epo) Rolementioning
confidence: 90%
See 1 more Smart Citation
“…On studying the blood flow of the human pretibial muscle by means of 133 Xe clearance, Buemi et al [22] found an EPO-induced reduction in postischemic vasodilation. Moreover, in anesthetized rats subjected to hemorrhagic shock by intermittent bleeding, EPO administration significantly increased the mean arterial pressure, the survival time, and the percentage of animals surviving with respect to untreated controls [23] . EPO also seems to be able to inhibit acetylcholine-induced cutaneous vasodilation and can stimulate the endothelial release of endothelin and inhibit nitric oxide, a potent vasodilator [24] .…”
Section: Ph: the Erythropoietin (Epo) Rolementioning
confidence: 90%
“…Remodeling operated by endothelial progenitor cells [17] In vivo effect on the PAP of polycythemia [21] Structural adaptation to hematological viscosity enhancement [18,20] Acute EPO administration in shocked rats [23] Interstitial and perivascular fibrosis [29] Upregulation of EPO receptor in the lung vessels [30] Clinical Models Acute EPO administration in shocked humans [25] Acute EPO administration in chronic cor pulmonale [26] …”
Section: Animal Modelsmentioning
confidence: 99%
“…The hormone, in fact, seems to be able to modify the kinetics of platelets and of the white cells [I], and it seems able to considerably modify endothelial activity [2] and vascular tone [3,4]. In previous studies.…”
Section: Doses Of Recombinant Erythropoietinmentioning
confidence: 99%
“…The vasoactive action of erythropoietin was also recently utilized in extreme hemodynamic conditions occurring during hemorrhagic shock [12]. The study was conducted on anesthetized rats, in which irreversible hemorrhagic shock was obtained through intermittent bleeding of the artery for 20 min, until a mean arterial pressure of 25–30 mm Hg was achieved.…”
mentioning
confidence: 99%